Health information technology capacity at federally qualified health centers: a mechanism for improving quality of care - Frimpong Jemima A; Jackson Bradford E; Stewart LaShonda M; Singh Karan P; Rivers Patrick A; Bae Sejong (BMC, 2013)
Abstract Background The adoption of health information technology has been recommended as a viable mechanism for improving quality of care and patient health outcomes. However, the capacity of health information technology (i.e., availability and use of multiple and advanced functionalities), particularly in federally qualified health centers (FQHCs) on improving quality of care is not well understood. We examined associations between health information technology (HIT) capacity at FQHCs and quality of care, measured by the receipt of discharge summary, frequency of patients receiving reminders/notifications for preventive care/follow-up care, and timely appointment for specialty care. Methods The analyses used 2009 data from the National Survey of Federally Qualified Health Centers. The study included 776 of the FQHCs that participated in the survey. We examined the extent of HIT use and tested the hypothesis that level of HIT capacity is associated with quality of care. Multivariable logistic regressions, reporting unadjusted and adjusted odds ratios, were used to examine whether 'FQHCs' HIT capacity' is associated with the outcome measures. Results The results showed a positive association between health information technology capacity and quality of care. FQHCs with higher HIT capacity were significantly more likely to have improved quality of care, measured by the receipt of discharge summaries (OR=1.43; CI=1.01, 2.40), the use of a patient notification system for preventive and follow-up care (OR=1.74; CI=1.23, 2.45), and timely appointment for specialty care (OR=1.77; CI=1.24, 2.53). Conclusions Our findings highlight the promise of HIT in improving quality of care, particularly for vulnerable populations who seek care at FQHCs. The results also show that FQHCs may not be maximizing the benefits of HIT. Efforts to implement HIT must include strategies that facilitate the implementation of comprehensive and advanced functionalities, as well as promote meaningful use of these systems. Further examination of the role of health information systems in clinical decision-making and improvements in patient outcomes are needed to better understand the benefits of HIT in improving overall quality of care.